2014
DOI: 10.1039/c4em00289j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of organic nitrogen in septic-impacted groundwater

Abstract: 27Dissolved inorganic and organic nitrogen levels are elevated in aquatic systems due to 28 anthropogenic activities. Dissolved organic nitrogen (DON) arises from various sources, and its 29 impact could be more clearly constrained if specific sources were identified and if the molecular-30 level composition of DON were better understood. In this work, the pharmaceutical 31 carbamazepine was used to identify septic-impacted groundwater in a coastal watershed. Using 32 ultrahigh resolution mass spectrometry dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…In contrast, N-containing formulas could not be assigned to any peaks observed using negative ESI FT-ICR MS in primary or secondary effluent (Tseng et al, 2013). While compounds with amine functional groups should ionize well in positive mode (Arnold et al, 2014), the interpretation of positive mode ESI spectra is complicated by the presence of sodium adducts (Koch et al, 2005); this challenge may explain why positive mode ESI data of wastewater-related samples has not been previously reported. To address this issue, both [M+H] + and [M+Na] + ions were considered for the assignment of CHON formulas (Koch et al, 2005) and only formulas that were part of a +CH 2 or (+CH 4 – O) homologous series were considered (Koch et al, 2007; Kujawinski and Behn, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, N-containing formulas could not be assigned to any peaks observed using negative ESI FT-ICR MS in primary or secondary effluent (Tseng et al, 2013). While compounds with amine functional groups should ionize well in positive mode (Arnold et al, 2014), the interpretation of positive mode ESI spectra is complicated by the presence of sodium adducts (Koch et al, 2005); this challenge may explain why positive mode ESI data of wastewater-related samples has not been previously reported. To address this issue, both [M+H] + and [M+Na] + ions were considered for the assignment of CHON formulas (Koch et al, 2005) and only formulas that were part of a +CH 2 or (+CH 4 – O) homologous series were considered (Koch et al, 2007; Kujawinski and Behn, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, negative mode CHON formulas in the protein-like (i.e., aliphatic) and lignin-like regions were found in tertiary wastewater effluent (Mesfioui et al, 2012) and DOM derived from the sludge of continuously-stirred tank biogas reactors (Shakeri Yekta et al, 2012), which also contains protein-derived compounds of human and microbial origin. Although positive mode CHON formulas have not been previously reported in wastewater, they have been identified in septic-impacted groundwater using FT-ICR MS (Arnold et al, 2014). The CHON formulas in the septic-impacted samples were found in the lipid- and protein-like regions, in agreement with the Nine Springs samples.…”
Section: Resultsmentioning
confidence: 99%
“…Solid phase extraction with PPL is in fact, currently the most popular choice for highthroughput isolation of DOM (Arnold et al, 2014;Flerus et al, 2012;Lawson et al, 2014;Roth et al, 2013). We have chosen PPL for extracellular metabolite extraction so that the LC-MS metabolomics data sets from our field and laboratory samples are comparable, and so that they can dovetail with other DOM measurements.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Kroeger et al () reported a positive correlation between groundwater DON concentrations and population density. Arnold et al () analyzed the molecular‐level composition of groundwater DON to demonstrate that septic systems were a dominant source of DON. However, others have reported that DON is predominantly derived from natural sources.…”
Section: Introductionmentioning
confidence: 99%